Variations in Abdominal Aortic Aneurysm Care: A Report From the International Consortium of Vascular Registries. Issue 24 (13th December 2016) - Beck, Adam W.; Sedrakyan, Art; Mao, Jialin; Venermo, Maarit; Faizer, Rumi; Debus, Sebastian; Behrendt, Christian-Alexander; Scali, Salvatore; Altreuther, Martin; Schermerhorn, Marc; Beiles, Barry; Szeberin, Zoltan; et al.
Abstract : Background: This project by the ICVR (International Consortium of Vascular Registries), a collaboration of 11 vascular surgical quality registries, was designed to evaluate international variation in the contemporary management of abdominal aortic aneurysm (AAA) with relation to recommended treatment guidelines from the Society for Vascular Surgery and the European Society for Vascular Surgery. Methods: Registry data for open and endovascular AAA repair (EVAR) during 2010 to 2013 were collected from 11 countries. Variations in patient selection and treatment were compared across countries and across centers within countries. Results: Among 51 153 patients, 86% were treated for intact AAA (iAAA) and 14% for ruptured AAA. Women constituted 18% of the entire cohort (range, 12% in Switzerland–21% in the United States; P <0.01). Intact AAAs were repaired at diameters smaller than recommended by guidelines in 31% of men (<5.5 cm; range, 6% in Iceland–41% in Germany; P <0.01) and 12% of women with iAAA (<5 cm; range, 0% in Iceland–16% in the United States; P <0.01). Overall, use of EVAR for iAAA varied from 28% in Hungary to 79% in the United States ( P <0.01) and for ruptured AAA from 5% in Denmark to 52% in the United States ( P <0.01). In addition to the between-country variations, significant variations were present between centers in each country in terms of EVAR use and rate of small AAA repair. Countries that more frequently treated small AAAs tended to use EVAR more frequently (trend: correlation coefficient, 0.51; P =0.14). Octogenarians made up 23% of all patients, ranging from 12% in Hungary to 29% in Australia ( P <0.01). In countries with a fee-for-service reimbursement system (Australia, Germany, Switzerland, and the United States), the proportions of small AAA (33%) and octogenarians undergoing iAAA repair (25%) were higher compared with countries with a population-based reimbursement model (small AAA repair, 16%; octogenarians, 18%; P <0.01). In general, center-level variation within countries in the management of AAA was as important as variation between countries. Conclusions: Despite homogeneous guidelines from professional societies, significant variation exists in the management of AAA, most notably for iAAA diameter at repair, use of EVAR, and the treatment of elderly patients. ICVR provides an opportunity to study treatment variation across countries and to encourage optimal practice by sharing these results. Abstract : Supplemental Digital Content is available in the text.